2023
DOI: 10.1111/vsu.13956
|View full text |Cite
|
Sign up to set email alerts
|

The effect of flushing of the common bile duct on hepatobiliary markers and short‐term outcomes in dogs undergoing cholecystectomy for the management of gall bladder mucocele: A randomized controlled prospective study

Abstract: Objective To determine the effect of flushing of the common bile duct (CBD) on hepatobiliary markers and short‐term outcome in dogs undergoing cholecystectomy for the management of gallbladder mucocele (GBM). Study design Randomized, controlled, prospective study. Animals Thirty‐two client‐owned dogs. Methods Dogs were allocated randomly to either a “flush” group or a “non‐flush group.” Flushing was performed in a normograde fashion, followed by a routine cholecystectomy. Data collected included presenting cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
(75 reference statements)
0
2
0
Order By: Relevance
“…Acute pancreatitis carries a high mortality rate in veterinary medicine, emphasizing the clinical significance of this complication [ 30 ]. Previous studies have shown that CBD catheterization, regardless of the approach, can increase surgical time without significant postoperative bilirubin level improvement [ 31 , 32 ]. This suggests that CBD flushing may lead to the reflux of biliary secretions into the pancreatic duct, potentially causing pancreatitis, or result in trauma to the major duodenal papilla, leading to inflammation and temporary occlusion of the pancreatic duct orifice.…”
Section: Discussionmentioning
confidence: 99%
“…Acute pancreatitis carries a high mortality rate in veterinary medicine, emphasizing the clinical significance of this complication [ 30 ]. Previous studies have shown that CBD catheterization, regardless of the approach, can increase surgical time without significant postoperative bilirubin level improvement [ 31 , 32 ]. This suggests that CBD flushing may lead to the reflux of biliary secretions into the pancreatic duct, potentially causing pancreatitis, or result in trauma to the major duodenal papilla, leading to inflammation and temporary occlusion of the pancreatic duct orifice.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, although elevated MUC1 expression may not be a direct factor in mucus accumulation, it may have an indirect effect on the pathophysiology of GBM. To investigate the relationship between the severity of GBM and the expression level of MUC1, we examined the correlation between MUC1 gene expression and blood test markers related to the outcome of GBM cases such as total bilirubin, C-reactive protein, alkaline phosphatase, and alanine aminotransferase [ 4 , 13 , 15 ], but none of the correlations between these markers and MUC1 were significant (data not shown). Further studies to examine the protein expression level of MUC1 in gallbladder epithelial cells of animals with GBM and the influence of increased expression of MUC1 on GBM are needed.…”
Section: Discussionmentioning
confidence: 99%